Architexture: space, form, and the late modernist novel - Zimmerman, Emma (2016)
This thesis sets out to facilitate an interdisciplinary dialogue between literature and architecture by drawing specific connections between the architectural elements of the twentieth-century built environment and the literary representation of that environment in the late modernist novel. Focusing on the mid-century work of three modernist women writers – Elizabeth Bowen, Jean Rhys, and Virginia Woolf – I argue that the architectural spaces they negotiate, and their specific articulation of those spaces, offer important insights into modernity’s crisis of home, belonging, and identity. Moreover, arguing that this crisis is exacerbated in the mid-century by the Second World War, I advance current understandings of ‘late modernism’. In particular, I provide detailed evidence of how these writers collectively respond to the architectural instabilities of the mid-century by developing the anxious forms of high modernist urbanism. Each chapter comprises an extended author-specific case study that brings together critical and theoretical debates on space and place through close readings of pertinent architectural themes and forms: Bowen and architectural ruination, Rhys and the architectural uncanny, and Woolf and architectural ambivalence. Throughout these chapters I demonstrate how the late modernist novel complicates Martin Heidegger’s conservative and mythic conception of the dwelling place through representing the built environment in terms of flux and interchange, thus playing an important role in (re)imagining and (re)constructing understandings of architectural space and place. Taking a literary geographic approach, but moving beyond the existing focus on ‘textuality’, I argue for an increased awareness of the immersive ‘textures’ of space and fiction. Developing literary geographic practice to take better account of architecture and affect, I thus establish a new vocabulary for elaborating the interdisciplinary connections between literature and architecture: what I term a ‘critical literary architexture’.